2017
DOI: 10.18632/oncotarget.16529
|View full text |Cite
|
Sign up to set email alerts
|

Monoglyceride lipase deficiency affects hepatic cholesterol metabolism and lipid-dependent gut transit in ApoE−/− mice

Abstract: Monoglyceride lipase (MGL) hydrolyzes monoglycerides (MGs) to glycerol and fatty acids. Among various MG species MGL also degrades 2-arachidonoylglycerol (2-AG), the most abundant endocannabinoid and potent activator of cannabinoid receptors (CBR) 1 and 2. MGL-knockout (−/−) mice exhibit pronounced 2-AG accumulation, but lack central cannabimimetic effects due to CB1R desensitization. We have previously shown that MGL affects plaque stability in apolipoprotein E (ApoE)−/− mice, an established animal model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…1G) with increased intestinal cholesterol (Chol) excretion (Abcg5) but unchanged Abcg8 and other lipid transporters Npc1l1, Srb1, and cluster of differentiation 36 (Cd36) (supplemental Fig. S1C) in accordance with a previous report (25). This indicates that reduced lipid absorption also contributes to decreased obesity in MGL / mice.…”
Section: Mgl Deficiency Protects From Hepatic Steatosis and Weight Gasupporting
confidence: 90%
See 3 more Smart Citations
“…1G) with increased intestinal cholesterol (Chol) excretion (Abcg5) but unchanged Abcg8 and other lipid transporters Npc1l1, Srb1, and cluster of differentiation 36 (Cd36) (supplemental Fig. S1C) in accordance with a previous report (25). This indicates that reduced lipid absorption also contributes to decreased obesity in MGL / mice.…”
Section: Mgl Deficiency Protects From Hepatic Steatosis and Weight Gasupporting
confidence: 90%
“…The discrepancy between diminished body and augmented adipose fat weight turned our attention to investigate intestinal malabsorption as a possible mechanistic explanation for our findings. Intestinal malabsorption was already described in a recent study, in which Vujic et al (25) crossed ApoE / with MGL / mice to potentiate the effects of disrupted lipid signaling and exacerbate hyperlipidemia. In addition, it was shown that delayed gastric emptying and reduced gut motility may contribute to reduced FA uptake and Chol absorption in double-KO animals (25).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Fractional cholesterol absorption was assessed in chow diet-fed male mice as described [ 18 ]. Briefly, animals were gavaged with 100 μl corn oil containing 0.2% cholesterol, 0.2 μCi [ 3 H]sitostanol, and 0.1 μCi [ 14 C] cholesterol (both from ARC Inc, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%